Effects of tibolone on markers of bone metabolic activity in postmenopausal women - Marić-Krejović Snežana; Živanović Aleksandar; Živanović Sandra; Marković Rade (Journal of Medical Biochemistry, 2012)
Osteoporosis, a systemic disease of the bones, is a serious health and socio-economic problem because of its consequences, i.e. broken bones. It is believed that 10% of the world's population suffers from osteoporosis and it affects mostly postmenopausal women (postmenopausal osteoporosis). Tibolone is a synthetic steroid that has estrogenic, androgenic, and progestagenic properties. It has been used primarily for the prevention of postmenopausal osteoporosis and treatment of climacteric symptoms. The research included a group of 40 postmenopausal women with osteopenia treated with tibolone. The control group included 40 postmenopausal women who were not taking any medication. Control group patients were older (54.5 ± 9.84) than the patients treated with tibolone (51.6 ± 6.22). Bone metabolic activity was evaluated using osteocalcin (N-MID osteocalcin) for bone formation and CTX I for bone resorption. Blood samples were taken before therapy was introduced and 3 months after its introduction. The average value of osteocalcin after three months of tibolone therapy was 26.32 ±3.312 ng/mL compared to the average osteocalcin value prior to therapy of 29.6 ± 3.343 ng/mL. The average value of CTX I three months after tibolone therapy of 0.2870 ± 0.0783 ng/mL was lower compared to the average CTX I value before the therapy of 0.4539 ± 0.1144 ng/mL. Our results show the efficacy of tibolone in preventing bone loss, which was highly statistically significant. They also reveal its suppressive effects on bone formation and resorption, but these effects are statistically less significant. Tibolone significantly reduces the level of bone resorption in postmenopausal women with osteopenia. Its effects on bone formation are less expressed. The parameters of bone metabolic activity are a very useful diagnostic means in the evaluation of tibolone effects on bone metabolic activity and in the prognosis of bone mass loss.